(untitled) (Journal of Atomic and Molecular Sciences, 2016)
The appropriate metric of quantum speed limit for the triatomic molecules is discussed using a generalized geometric approach. The researches show the quantum Fisher information metric is tighter than the Wigner-Yanase information metric in realistic molecular dynamical evolution. The quantum speed limit metric is related to the initial evolution state of molecules.